The Impact of Student Teams Achievement Divisions (STAD) Learning Method on Long Jump Performance - Dewi Septaliza; Edi Sopran Lubis (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research aims to investigate the influence of the Student Team Achievement Divisions (STAD) learning method on students' long jump performance. The STAD learning method is an approach that encourages collaboration and interaction among students in the form of teams, with a focus on both group and individual achievements. Long jump was chosen as the research context due to its involvement in complex physical and technical aspects, requiring a combination of motor skills and conceptual understanding. The research method used is an experimental method, with a "one group pretest-posttest" design. The study involves a sample of 50 male students at MTs Miftahul Ulum Pangkalan Balai. The instrument used is an assessment of long jump performance. The assessment of long jump in this research covers both the process and the outcome, including the distance achieved in the jump. Data analysis is conducted using the t-test. The results of the data analysis show that because the calculated t-value is 5.87 > the tabulated t-value of 2.00. The findings of this study indicate a significant influence of the STAD method on the improvement of long jump skills among students at MTs Miftahul Ulum Pangkalan Balai. This research provides a significant contribution to our understanding of the impact of the STAD method on students' long jump results, forming the basis for the development of more effective and sustainable learning approaches in the field of sports.